Persaingan Usaha Tidak Sehat Akibat Konsep Likuidasi Dalam Hukum Kepailitan Indonesia - Putri, Anggia Maharani; Marwanto, Marwanto (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 02 (2023)DO - 10.24843/AC.2023.v08.i02.p6, 2023)
This research was conducted to understand how the concepts in the bankruptcy law have an impact on unfair business competition and the efforts that need to be taken to overcome these problems. This is because the bankruptcy institution has not provided definite protection to the parties, thus creating unfair business competition between creditors and debtors. normative research is use to be the refference by using a conceptual approach and statutory approach to study regulations in the face of existing facts. This research originates from laws and regulations and other supporting sources. The results obtained in the analysis carried out are that the concept used contains elements of general confiscation of all assets belonging to the debtor with simple requirements making it easy for creditors to bankrupt the company and bring about unfair business competition between companies. Overcoming these problems, it is important that the government to take action to change the concept of liquidation towards company reorganization and changes to bankruptcy requirements.